Comparative Analysis of Machine Learning Algorithms on Surface Enhanced Raman Spectra of Clinical Staphylococcus Species - Tang, Jia-Wei; Liu, Qing-Hua; Yin, Xiao-Cong; Pan, Ya-Cheng; Wen, Peng-Bo; Liu, Xin; Kang, Xing-Xing; Gu, Bing; Zhu, Zuo-Bin; Wang, Liang (Frontiers in Microbiology, 2021)
Raman spectroscopy (RS) is a widely used analytical technique based on the detection of molecular vibrations in a defined system, which generates Raman spectra that contain unique and highly resolved fingerprints of the system. However, the low intensity of normal Raman scattering effect greatly hinders its application. Recently, the newly emerged surface enhanced Raman spectroscopy (SERS) technique overcomes the problem by mixing metal nanoparticles such as gold and silver with samples, which greatly enhances signal intensity of Raman effects by orders of magnitudes when compared with regular RS. In clinical and research laboratories, SERS provides a great potential for fast, sensitive, label-free and non-destructive microbial detection and identification with the assistance of appropriate machine learning algorithms. However, choosing an appropriate algorithm for a specific group of bacterial species remains challenging, because with the large volumes of data generated during SERS analysis, not all algorithms could achieve a relatively high accuracy. In this study, we compared 3 unsupervised machine learning methods and 10 supervised machine learning methods, respectively, on 2752 SERS spectra from 117 Staphylococcus strains belonging to 9 clinically important Staphylococcus species in order to test the capacity of different machine learning methods for bacterial rapid differentiation and accurate prediction. According to the results, DBSCAN showed the best clustering capacity (Rand index 0.9733) while convolutional neural network (CNN) topped all other supervised machine learning methods as the best model for predicting Staphylococcus species via SERS spectra (ACC 98.21%, AUC 99.93%). Taken together, this study shows that machine learning methods are capable of distinguishing closely related Staphylococcus species and therefore have great application potentials for bacterial pathogen diagnosis in clinical settings.